Tinjauan Yuridis Mengenai Hak-Hak Khusus Pekerja Perempuan Berdasarkan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan - Sonhaji Sonhaji (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
Abstract Women are naturally different from the men so that women have special rights granted while men are not given. Female workers/laborers likewise have special rights such as the right to leave miscarriage, the right to maternity leave, menstrual leave, the right to a shuttle if employed at night, and so forth. The special rights of female workers/laborers like these should be considered either by the company or by the workers/laborers women themselves. PT. Dian Andilta Utama is not yet fully apply the special rights of female workers/laborers, obstacles in implementing the special rights of female workers/laborers are in the application of the provision of menstrual leave and leave miscarriage, efforts to overcome obstacles in the implementation of the exclusive rights of female workers/laborers are female workers/laborers should correctly understand the content of the employment agreement is given at the beginning will sign a cooperation agreement. Keywords: Special Rights Of Women Workers, Act No. 13 of 2003 Abstrak Perempuan secara kodrati berbeda dengan laki-laki sehingga perempuan memiliki hak-hak khusus yang diberikan sedangkan laki-laki tidak diberikan.Pekerja/ buruh perempuan demikian pula memiliki hak-hak khusus seperti hak cuti keguguran kandungan, hak cuti melahirkan, hak cuti haid, hak mendapatkan antar jemput jika dipekerjakan pada malam hari, dan sebagainya.Hak-hak khusus pekerja/ buruh perempuan seperti ini sudah seharusnya diperhatikan baik oleh pihak perusahaan maupun oleh para pekerja/ buruh perempuan itu sendiri. PT. Dian Andilta Utama belum sepenuhnya menerapkan hak-hak khusus pekerja/ buruh perempuan, hambatan dalam menerapkan hak-hak khusus pekerja/ buruh perempuan adalah dalam penerapan pemberian cuti haid dan cuti keguguran, upaya mengatasi hambatan dalam penerapan hak-hak khusus pekerja/ buruh perempuan adalah pekerja/ buruh perempuan harus memahami secara benar isi dari perjanjian kerja yang diberikan pada saat awal akan menandatangani perjanjian kerja. Kata kunci: Hak-Hak Khusus Pekerja Perempuan, Undang-Undang Nomor 13 Tahun 2003